Participative Management as a Critical Ingredient for TQM - Parumasur, Sanjana Brijball (Journal of Economics and Behavioral Studies, 2013)
Increasing competition has necessitated the need for human capital to ensure continuous improvement in quality in order to secure customer satisfaction, loyalty and sustainable development. This study aims to assess managerial perceptions of the extent and nature of participative management (delegation, involvement/empowerment, coaching, supportive leadership style) that takes place in the organization in efforts to achieve total quality management. Biographical influences on these managerial perceptions are also assessed. A sample of 202 managers (middle, senior, top) was drawn using a stratified random sampling technique. Data was collected using a pre-coded, self-developed questionnaire and analyzed using descriptive and inferential statistics. The findings reflect managers believe that participative management takes place at a moderate pace in the organization with the greatest focus being on coaching, followed by supportive leadership style, delegation and lastly, involvement/empowerment. Based on the results, recommendations for bringing about effective delegation, enhancing involvement/empowerment, ensuring valuable coaching and nurturing a supportive leadership style in efforts to accomplish TQM are presented.